2010
DOI: 10.1093/jac/dkq278
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a novel aminoglycoside, ACHN-490, against clinical isolates of Escherichia coli and Klebsiella pneumoniae from New York City

Abstract: The novel aminoglycoside ACHN-490 retains activity against most isolates of E. coli and K. pneumoniae, including multidrug-resistant strains. Additional studies examining the roles of efflux systems and outer membrane permeability alterations are recommended in isolates with reduced susceptibility to this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 14 publications
2
31
0
2
Order By: Relevance
“…Plazomicin demonstrated potent in vitro activity versus members of the family Enterobacteriaceae, including aminoglycoside-nonsusceptible E. coli and ESBL-producing E. coli and K. pneumoniae. Similar results have been reported by other investigators (13,16,17,(20)(21)(22)(23)(24). Furthermore, many of these studies also specifically evaluated the activity of plazomicin against collections of antimicrobial-resistant isolates (20)(21)(22).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Plazomicin demonstrated potent in vitro activity versus members of the family Enterobacteriaceae, including aminoglycoside-nonsusceptible E. coli and ESBL-producing E. coli and K. pneumoniae. Similar results have been reported by other investigators (13,16,17,(20)(21)(22)(23)(24). Furthermore, many of these studies also specifically evaluated the activity of plazomicin against collections of antimicrobial-resistant isolates (20)(21)(22).…”
Section: Discussionsupporting
confidence: 92%
“…Aggen et al (16) previously demonstrated that almost all common AMEs, with the exception of AAC(2=)-I, have no effect on the activity of plazomicin. Data published by Landman et al (17) support this finding. Of concern, however, the in vitro activity of plazomicin does appear to be compromised by the presence of ribosomal methylases, including the ArmA methylase and RmtC methylase (16,22).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…On day 5, a full PK time course was obtained which included the following time points: predose and 10, 15, 20, 30, 45, and 60 min and 1.5, 2, 2.5, 3,4,6,8,12,16, and 24 h after the start of the IV infusion.…”
Section: Ethicsmentioning
confidence: 99%
“…Plazomicin, a derivative of sisomicin, is a next-generation aminoglycoside that is in clinical development for the treatment of serious infections due to carbapenem-resistant Enterobacteriaceae. It has broad-spectrum in vitro activity against Klebsiella pneumoniae and other Gram-negative bacteria, including carbapenem-resistant strains (8)(9)(10)(11)(12). The agent has side-chain substituents that shield it from the action of most AMEs.…”
mentioning
confidence: 99%